2019
DOI: 10.1093/jn/nxz146
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Ethyl Glucuronide Can Be Used as a Biomarker of Habitual Alcohol Consumption in the General Population

Abstract: BackgroundAlcohol consumption is a frequently studied risk factor for chronic diseases, but many studies are hampered by self-report of alcohol consumption. The urinary metabolite ethyl glucuronide (EtG), reflecting alcohol consumption during the past 72 h, is a promising objective marker, but population data are lacking.ObjectiveThe objective of this study was to assess the reliability of EtG as a marker for habitual alcohol consumption compared with self-report and other biomarkers in the general population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…As shown in Figure 7 ethyl-β-D-glucuronide, a metabolite of alcohol consumption [38] was elevated only in participants consuming OJ (+11.9 ± 3.3, p < 0.0001) but was undetected in those consuming sucrose-SB; (p = 0.001 between groups). This metabolite was undetected among38st all participants at baseline.…”
Section: Ethyl-β-d-glucuronidementioning
confidence: 85%
See 2 more Smart Citations
“…As shown in Figure 7 ethyl-β-D-glucuronide, a metabolite of alcohol consumption [38] was elevated only in participants consuming OJ (+11.9 ± 3.3, p < 0.0001) but was undetected in those consuming sucrose-SB; (p = 0.001 between groups). This metabolite was undetected among38st all participants at baseline.…”
Section: Ethyl-β-d-glucuronidementioning
confidence: 85%
“…One interesting outcome of this study was the increase in ethyl-β-D-glucuronide, a well-known biomarker for monitoring ethanol intake [38,64], in the plasma of subjects consuming OJ. This metabolite was not observed at baseline and was not observed after intervention in participants consuming sucrose-SB.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As per evident ethical and logistical reasons, the main body of evidence relies on epidemiological studies of associative nature which carry several limitations such as the quantification of alcohol consumption. In the future, these studies should include reliable measurements of biological biomarkers of alcohol exposure such as urinary ethyl glucuronide [144] which may better reflect short-term and habitual alcohol consumption than self-reported intake and should also include repeated measures over time.…”
Section: Discussionmentioning
confidence: 99%
“…CDT has been the most commonly used biomarker to confirm chronic alcohol consumption for years, although the sensitivity and specificity vary considerably between different studies, and numerous confounders could influence the results, including age, sex, and the stage of liver disease [ 155 , 156 ]. EtG can be detected in the urine or hair, has a much longer detection window, and a higher specificity than CDT, although biological variability (e.g., medications and foods) still exists and may complicate the interpretation of the results [ 157 , 158 ]. Several studies have compared the detection ability of these biomarkers and revealed conflicting results [ 154 , 157 , 159 , 160 ].…”
Section: Diagnosismentioning
confidence: 99%